2017
DOI: 10.1161/strokeaha.117.017343
|View full text |Cite
|
Sign up to set email alerts
|

Statin Adherence Is Associated With Reduced Recurrent Stroke Risk in Patients With or Without Atrial Fibrillation

Abstract: Background and Purpose-Outpatient statin use reduces the risk of recurrent ischemic stroke among patients with stroke of atherothrombotic cause. It is not known whether statins have similar effects in ischemic stroke caused by atrial fibrillation (AFib). Methods-We studied outpatient statin adherence, measured by percentage of days covered, and the risk of recurrent ischemic stroke in patients with or without AFib in a 21-hospital integrated healthcare delivery system. Results-Among 6116 patients with ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Adherence to statin medication was associated with lower risk of recurrent ischemic stroke, hemorrhagic stroke, and acute coronary events 1 year after statin initiation in patients with ischemic stroke or TIA [22]. Another study suggested that the relationship between statin adherence and reduced recurrent stroke risk is similar regardless of atrial fibrillation status [23]. Recent reports using nationwide health claim data in South Korea showed that good adherence was associated with lower risk of CV events [24].…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to statin medication was associated with lower risk of recurrent ischemic stroke, hemorrhagic stroke, and acute coronary events 1 year after statin initiation in patients with ischemic stroke or TIA [22]. Another study suggested that the relationship between statin adherence and reduced recurrent stroke risk is similar regardless of atrial fibrillation status [23]. Recent reports using nationwide health claim data in South Korea showed that good adherence was associated with lower risk of CV events [24].…”
Section: Discussionmentioning
confidence: 99%
“…[104][105][106] In randomized controlled trials (RCTs), statins reduced the incidence of new-onset as well as recurrent AF; 107-109 their use is also associated with a decrease in AF-related thromboembolic events. 110,111 At the same time, the use of statins is followed by an improvement in abnormal diastolic filling dynamics [112][113][114] as well as by reduced risk for new-onset HF with the features of HFpEF. 115,116…”
Section: Statinsmentioning
confidence: 99%
“…A recent observational study from a large database evaluated the risk of recurrent stroke in patients with or without atrial fibrillation who took statins after their stroke. 13 The risk of recurrent stroke was strongly related to adherence with the statin prescription and adherence in both groups, suggesting that statins may reduce recurrent stroke risk in stroke related to atrial fibrillation. Though intriguing, this study is not definitive, and the results may have been affected by bias and confounding.…”
Section: Use Of Statins After Ischemic Strokementioning
confidence: 91%